Analisis Implementasi Kewenangan Camat Menurut UU No. 32/2004 (Studi kantor Kecamatan Tanjung Selor dan Tanjung Palas, Bulungan Kalimantan Utara) - Syaini, Syaini; Pribadi, Ulung (Universitas Muhammadiyah Yogyakarta, 2016)
The purpose of this research is to describe and analize the implementation of Authory of the head of Sub- Districtbased on law No. 32 of 2004 on Regional Government (studies on the office of Tanjung Selor and Tanjung Palas Sub-District of Bulungan, North Berneo) about the implementation in terms of sub-district in Tanjung Selor and TanjungPalas sub-District of Bulungan. Based of the law No. 32 of 2004 concerning local government in which the delegationof authory from the regent to the head of sub-distruct is a from of desentralized system of govenment in strengtheningthe organizational structure at districtand maximizing the service. The reseach method used a descriptive studywith a qualitative approach. Reseachs used data collection techniques though interviews, observation, and documents.The focus of reseach is the Analycis on the implementation of Authory of the head of Sub-Distruct based onlaw No. 32 of 2004 on regional Govenment (studies on the office of Tanjung Selor and Tanjung Palas Sus Distruct,Distruct of Bulungan, North Borneo). Based on the results of a study conducted reseachers at Tanjung Selor andTanjung Palas Sub-Distruct are there several problems associated with the authory of the head of sub-district, such asthe coordination on the soceity development, the coordination and maintenance of public intrasstructure and facilities,the coordination of govenments activities in sub district level, and village in order to carry out community serviceinto a scope of duties that can not be carried out optimally. The finding of this research is that in the implementationof the task is not in accordance with what is expeted, the authory i not yet clear, lack of community participation andlaw human resources in the sub-district office. The inhibiting factors are innefective communication, minimum resources,disposition and bureaucratic structures that do not fuction properly. It is suggersted that the service wouldbe optimal by revamping the Tnajung Selor and Tanjung Palas sub-district office..